Inter-Vehicle Communication: Emergency Message Delay Distributions - Kajackas, A.; Vindašius, A.; Stanaitis, Š. (Elektronika ir Elektrotechnika, 2009)
Road accidents and traffic jams are most important problems on the roads. To decrease the mentioned problems wireless inter-vehicle communication – WAVE can be used. The nearby cars send the emergency warning messages about their actions. In this paper, using NCTUns 5.0 environment, are analyzed the delay values of emergency message transmission in multi-hop link, based on legacy IEEE 802.11 and emerging IEEE 802.11p standard. Simulations show, that single message propagation is in permissible range even for 100 nodes. For controlled flood scenario node number increases delay exponentially. Ill. 10, bibl. 8, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).